2020
DOI: 10.2147/ndt.s289990
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cerebroprotein Hydrolysate, CH1, Ameliorates Chronic Focal Cerebral Ischemia Injury by Promoting White Matter Integrity via the Shh/Ptch-1/Gli-1 Signaling Pathway

Abstract: Purpose Strokes are devastating as there are no current therapies to prevent long-term neurological deficits. Previous studies reported that cerebroprotein hydrolysate (CH) plays a role in neuronal protection in acute phase after ischemic stroke, while the long-term effects of CH upon brain plasticity and neurological outcomes after stroke are still uncertain. To address these gaps, we assessed the effect of a new cerebroprotein hydrolysate, CH1, on long-term gray and white matter integrity as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…7 The free amino acids of 50–80% can enter brain neurons through the blood brain barrier (BBB) and strengthen protein synthesis in the brain. 10 , 11 , 24 It can simulate similar pharmacodynamic characteristics of neurotrophic factors (NTFs), such as BDNF, NGF, and serum insulin-like growth factor-1 (IGF-1). 8 , 10 , 24 In the current experiment, it has been found that CH-I can promote the repair of neurons and subsequently improve the dementia symptoms and delay the aggravation of dementia lesions of vascular dementia (VaD) rats by elevating the level of IGF-1 in VaD rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 The free amino acids of 50–80% can enter brain neurons through the blood brain barrier (BBB) and strengthen protein synthesis in the brain. 10 , 11 , 24 It can simulate similar pharmacodynamic characteristics of neurotrophic factors (NTFs), such as BDNF, NGF, and serum insulin-like growth factor-1 (IGF-1). 8 , 10 , 24 In the current experiment, it has been found that CH-I can promote the repair of neurons and subsequently improve the dementia symptoms and delay the aggravation of dementia lesions of vascular dementia (VaD) rats by elevating the level of IGF-1 in VaD rats.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 10 , 24 In the current experiment, it has been found that CH-I can promote the repair of neurons and subsequently improve the dementia symptoms and delay the aggravation of dementia lesions of vascular dementia (VaD) rats by elevating the level of IGF-1 in VaD rats. 14 Cao et al 11 have found that continuous intraperitoneal injection of CH-I 14d to MCAO mice can improve the mNSS score, promote neuronal survival, and significantly improve infarct size in mice. BDNF is among the most abundant NTFs in brain tissue, mainly expressed in the synapse of the hypothalamus, cortex, and the basal part of the forebrain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 In a recent study, it was found that CH-I mitigated stroke-induced white matter injury and facilitated axonal plasticity in the late stage after stroke. 19 CBL can improve the cognitive ability and general function of VaD patients, 20 attenuate apoptosis of thalamic neurons 21 and improve the neurological function in middle cerebral artery occlusion (MCAO) rats. 22 Therefore, we speculate that CH-I and CBL may have similar neuroprotective effects.…”
Section: Introductionmentioning
confidence: 99%